GENDER CONDITIONING OF EMOTIVITY IN THE AUTHOR’S WORLD PERCEPTION - Tsyntar, Natalia (ВИКЛАДАННЯ АНГЛІЙСЬКОЇ МОВИ В ВІЙСЬКОВИЙ ЧАС: ПРОБЛЕМИ ТА МОЖЛИВОСТІ ДЛЯ РОЗБУДОВИ ГРОМАДИ ТА СОЦІАЛЬНИХ ЗМІН: тези доповідей (англ. мовою) / Укл. О.Ільєнко, М. Цегельська, Л. Кузнецова. – Львів : ПП „Марусич”, 2023., 2023)
A human is an emotional being by nature. The unity of feeling, thinking, analysis, spirituality and intelligence that are the components of anthropomorphism, makes it possible to gain a deeper understanding of both the external and internal world [3]. Human emotions, on the one hand, are a part of reality itself, i.e. refl ected objects of the real picture of the world and, on the other hand, they participate in the formation of the linguistic picture of the world: a person is an active subject of the process of refl ection and language is its means, emotions are one of the forms of refl ecting the objective reality. The doctrine of the interaction of ethnos, logos and pathos where the latter appeals to emotions, proves the inseparability of the feelings from any speech. Therefore, gender differences in the expression of emotions depend primarily on the ethno-cultural standards and norms of a certain society. Men are more likely to control emotions and restrain their expression. At the same time, women’s emotional intelligence is more closely related to the cognitive processes of understanding emotions.
Keywords: emotivity, exclamatory sentences, repetitions, positive emotions, negative emotions.